Development of intermodal transport in new European Union states - Šakalys, Algirdas; Palšaitis, Ramūnas (Transport, 2006)
The article presents the main outcomes of the NAS‐ITIP project (FRAMEWORK'5) on the situation of intermodal transport in new European Union states. The main measures for the development of intermodal transport in these countries are highlighted: modernisation and development of intermodal infrastructure; innovative technologies; establishment of modern logistics centres. Recommendations to EC and national governmental institutions for the development of intermodality are proposed.First Published Online: 27 Oct 2010